2016
DOI: 10.1002/jcb.25513
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Prevents Mouse Embryonic Stem Cell Differentiation Through Regulation of Gene Expression, Cell Signaling, and Control of Cell Proliferation

Abstract: Nitric oxide (NO) delays mouse embryonic stem cell (mESC) differentiation by regulating genes linked to pluripotency and differentiation. Nevertheless, no profound study has been conducted on cell differentiation regulation by this molecule through signaling on essential biological functions. We sought to demonstrate that NO positively regulates the pluripotency transcriptional core, enforcing changes in the chromatin structure, in addition to regulating cell proliferation, and signaling pathways with key role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…In our study, more NO was released from ADSCs-iNOS than ADSCs. Tapia-Limonchi et al found that NO maintained embryonic stem cells (ESC) pluripotency and delayed ESC differentiation by regulating Gsk3-β/β-catenin and PI3K/Akt signaling pathways (Tapia-Limonchi et al, 2016). The effect of NO released from ADSCs iNOS on ADSC stemness required further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more NO was released from ADSCs-iNOS than ADSCs. Tapia-Limonchi et al found that NO maintained embryonic stem cells (ESC) pluripotency and delayed ESC differentiation by regulating Gsk3-β/β-catenin and PI3K/Akt signaling pathways (Tapia-Limonchi et al, 2016). The effect of NO released from ADSCs iNOS on ADSC stemness required further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more NO were released from ADSCs-iNOS than ADSCs. Tapia-Limonchi et al found that NO maintained embryonic stem cells (ESC) pluripotency and delayed ESC differentiation by regulating Gsk3-β/β-catenin and PI3K/Akt signaling pathways (Tapia-Limonchi et al, 2016). The effect of NO released from ADSCs iNOS on ADSC stemness required further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more NO was released from ADSCs-iNOS than ADSCs. Tapia-Limonchi et al (2016) found that NO maintained embryonic stem cells (ESC) pluripotency and delayed ESC differentiation by regulating Gsk3-β/β-catenin and PI3K/Akt signaling pathways. The effect of NO released from ADSCs iNOS on ADSC stemness required further investigation.…”
Section: Discussionmentioning
confidence: 99%